The Effect of the Education of Grandmothers on Their Attitude toward Breastfeeding - T Gharaei; L Amiri Farahani; SH Haghani; SB Hasanpoor-Azghady (Iran University of Medical Sciences, 2019)
Background & Aims: Grandmothers play a key role in the success of breastfeeding. The positive attitude of grandmothers toward breastfeeding largely influences the length of breastfeeding. The present study aimed to assess the effect of the education of grandmothers on their attitude toward breastfeeding. Materials & Methods: This clinical trial was conducted with a pretest-posttest design and a control group was conducted on 64 maternal grandmothers referring to Amir Al-Momenin Hospital in Tehran, Iran in 2018. The maternal grandmothers who met the inclusion criteria were selected via continuous sampling until the completion of the sample size and assigned to the groups of intervention (n=32) and control (n=32) weekly. In the intervention group, the maternal grandmothers attended two one-hour sessions of breastfeeding education with their primiparous daughters in weeks 1-34 and 35-37 of gestation, respectively. In the control group, the maternal grandmothers received no training, while they were provided with the educational contents after the two sessions. Data were collected using Iowa Infant Feeding Attitude Scale (IIFAS) before and immediately after the educational intervention. Data analysis was performed using descriptive and inferential statistics. Results: Independent t-test showed no significant difference in the mean score of the breastfeeding attitude between the intervention and control groups before intervention. However, a significant difference was observed in the mean score of the breastfeeding attitude immediately after the intervention between the control (60.12±7.53) and the intervention groups (74.21 ± 1.36) (P<0.001) as the obtained mean score was higher in the intervention group compared to the control group. In other words, the education of the grandmothers significantly increased the score of the breastfeeding attitude in the intervention group. Conclusion: According to the results, breastfeeding education of grandmothers could improve their attitude toward breastfeeding. Therefore, the presence of grandmothers in breastfeeding educational sessions could effectively enhance the attitude toward breastfeeding, thereby promoting exclusive breastfeeding.